Efficiency of Using the Diffie-Hellman Key in Cryptography for Internet Security - Anas Aljarah, Ghaith Alomari (Turkish journal of computer and mathematics education, 2021)
The businesses generate an “intranet” to hang about connected to the internet but secured from possible threats. Data integrity is quite a issue in security and  to preserve that integrity we tends to develop as to provides the better encryption processes for security. In this work  we will make a  encryption harder with enhanced public key encryption protocol for the  security and we will talk about the applications for proposed work. We will enhance the hardness in security by humanizing the Diffie-Hellman encryption algorithm by making changes or adding some more security codes in up to date algorithm. Network security has become more important to not public computer users, organizations,  and the military.With the start of the internet, security became a major disquiet and the history of security allows a better understanding of the emergence of security technology. The  internet structure itself allowed for many security threats  to  occur.When the architecture of the internet is modified it can decrease the possible attacks that can be sent across the network. Knowing the attack methods, allows  for  the suitable security to  appear. By means of the firewalls and encryption   mechanisms  many businesses protected themselves from the internet.The firms crank out an “internet" to hold around connected into this world wide web but procured from potential dangers. Data ethics is a significant dilemma in protection and also to conserve integrity we all are inclined to grow concerning furnishes exactly the encryption procedures such as the security. Inside this job we'll earn a encryption tougher using improved general security protocol to your own stability and we're going to discuss the software for projected work. We'll improve the hardness of stability by humanizing that the Diffie Hellman encryption algorithm by generating alterations or including a few far more stability codes up to date algorithm. Network safety has gotten more very important to perhaps not people users, associations, and also the army. With all the beginning of internet, stability turned into a significant vexation along with the foundation of safety makes it possible for a superior comprehension of the development of technology. Even the online arrangement itself enabled for most security dangers that occurs. After the structure of this world wide web is altered it could diminish the probable strikes which may be transmitted from the other side of the community. Recognizing the assault procedures, permits the acceptable stability to arise. With this firewalls and security mechanics many companies shielded themselves out of the world wide web.